The Voice of the Modern Bengali - Nasheet Rumy; Mohammed Andalib Saadullah (Docomomo Journal, 2022)
"You have to be a world man and a Bengali. It's impossible otherwise ... When I mention standing on one's own soil ... it is to find oneself, but not to find oneself and become stagnant. What I am seeking is to stand on one's own feet and to proceed forward. If for that reason I have to take two steps backward to go one step forward, I have no problem with that. I think that there is no other way of moving forward." Muzharul Islam, 1992